Self-Energized UAV-Assisted Scheme for Cooperative Wireless Relay Networks - Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara; Ponnimbaduge Perera T. D. Tarindu Dilshan; Ghrayeb A. Ali; Hasna M.O. Mazen (2020, 2020)
Title screen